The RSNA Pulmonary Embolism CT Dataset - Colak, Errol (Radiol Artif Intell, 2021)
Supplemental material is available for this article. Keywords: CT-Angiography, Diagnosis, Embolism/Thrombosis, Feature detection, Informatics, Pulmonary Arteries, Thorax